Abolishing Public Guarantees in the Absence of Market Discipline - Tobias Körner; Isabel Schnabel (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
This paper shows that the abolition of state guarantees to publicly owned banks in Germany resulted in an increase in funding costs at German savings banks. Rather than being the result of increased market discipline, the increase in funding costs is shown to be driven by spillover effects from German Landesbanken who themselves had suffered from the abolition of guarantees and who spread their own cost increase through the public banking network. Higher funding costs and the resulting drop in bank charter values translated into higher risk-taking at German savings bank. – – Dieser Beitrag zeigt, dass der Wegfall staatlicher Garantien öffentlich-rechtlicher Kreditinstitute in Deutschland (Anstaltslast und Gewährträgerhaftung) zu einem Anstieg der Refinanzierungskosten von Sparkassen geführt hat. Dies ist jedoch nicht auf eine strengere Marktdisziplinierung der Sparkassen zurückzuführen, sondern vielmehr auf Spill-over Effekte von Landesbanken, die ihrerseits direkt vom Wegfall der Garantien betroffen waren und ihre Kostennachteile innerhalb des Sparkassenverbundes weitergaben. Höhere Refinanzierungskosten der Sparkassen und daraus resultierende geringere Charter values führten zu einer höheren Risikonahme von Sparkassen.
Keywords: G21; G28; H11; L32; 330; public bail-out guarantees; savings banks; Landesbanken; market discipline; bank risk-taking; banking networks